IN TEACHING PEDAGOGICAL SCIENCES WAYS OF USING THE PEDAGOGICAL APPROACHES OF ALLOMALS IN THE I-RENESSANCE PERIOD (Academicia Globe: Inderscience Research, 2022)
The article provides In teaching pedagogical sciences ways of using the pedagogical approaches of allomals in the I-renessance period.